The Tragedies of Brazilian Higher Education - Knobel, Marcelo; Leal, Fernanda (International Higher Education, 2021)
Continuing reflection on critical policy changes in Brazilian higher education since President Bolsonaro assumed office in January 2019, this article presents what we call “a chronology of tragedies,” a review of events that have taken place since September 2019. These events reveal the ways through which federal policies continue to threaten university autonomy, even though the public higher education sector has proved to be fundamental to fighting the current COVID-19 pandemic.